CROSS-GENRE ANALYSIS OF PAREMIOLOGICAL PROLONGATIONS IN SLOVENIAN ACCORDING TO PERMJAKOV’S DISTINCTION BETWEEN EXTENSION AND ADDITION - Meterc, Matej; Mrvič, Rok (Proverbium - Yearbook, 2024)
The distinction between extension (Russian: razvjortyvanie) - a type of prolongation in which the meaning of the expression is preserved - and addition (Russian: dopolnenie), in which the meaning of the expression necessarily changes, was briefly but clearly presented by Permjakov. We are convinced that the consideration of the difference between extension and addition is very useful for phraseological and paremiological theory, as it is inextricably linked to the question of whether prolongation is a variant of an expression (in the case of extension) or a new expression (addition). We present paremias and humorous phrasemes created by addition or extension and highlight the genre differences between them. We also show how the difference between extension and addition can be recognized from the examples of use and explanations of meaning listed in the Slovenian paremiological dictionary. Data on the degree of familiarity of paremia among Slovenian speakers is given on the basis of a survey which was conducted in order to determine the Slovenian paremiological minimum.